Effect of Customer Relationship Management, Marketing Mix, Service Quality, Entrepreneurs Orientation to Competitive Advantages and Its Impact on Marketing Performance at Public Market - suparno, Endah Budiarti (Archives of Business Research, 2018)
The purpose of this research is to analyze and prove the influence of customer relationship management (CRM), marketing mix, service quality and entrepreneurship orientation to competitive advantage and marketing performance and to analyze and prove the influence of competitive advantage to market performance of public market in Surabaya. The population in this study is the market traders of the people at present more than 17.000. In this study, researchers measured the performance of PD Pasar Surya Surabaya marketing based on customer perception or tenants of the booth. So in this case the size of marketing performance is perceptual. The sample used is 135 traders. The amount is spread in 67 units of market managed by PD Pasar Surya Surabaya. The model to be used in this research is the model of causality or relationship. To test the proposed hypothesis, the analysis technique used is SEM (Structural Equation Modeling), with AMOS statistic software. The results of hypothesis testing: Customer relationship management significant effect on the competitive advantage of the public market in the city of Surabaya. Marketing mix significantly influence the competitive advantage of public market in Surabaya City. Service quality significantly influence the competitive advantage of public market in Surabaya City. The entrepreneurship orientation has a significant effect on the competitive advantage of public market in Surabaya City. Customer relationship management has a significant effect on marketing performance of public market in Surabaya City. Marketing mix significantly influence the marketing performance of public market in Surabaya City. Service quality has a significant effect on marketing performance of public market in Surabaya City. The entrepreneurship orientation has a significant effect on marketing performance of public market in Surabaya City. Competitive advantage significantly influence the marketing performance of public market in Surabaya